(untitled) (Journal of the College of Basic Education, 2022)
From the foregoing, it is clear to us that identifying the contents of the concepts of the terms mentioned in the research or the subject of the research gives a clear vision of the easy way to identify the terms that Islamic law is keen on investing and developing funds if that is consistent with its provisions. that. This care and attention given by the Sharia to investing money did not come in vain and without prior planning. Rather, there are material goals to satisfy human needs in various fields.